Chitosan surface modified hydrogel as a therapeutic contact lens. (9th December 2019) - Kazemi Ashtiani, Mohammad; Zandi, Mojgan; Shokrollahi, Parvin; Ehsani, Morteza; Baharvand, Hossein
Abstract : Therapeutic contact lenses have attracted significant attention during the last decades. In this study, we used chitosan‐conjugated poly(2‐hydroxyethyl methacrylate) (PHEMA) for contact lens application. We aimed to increase affinity of anionic drugs, which are used in treatment of eye diseases. In this regard, we evaluated delivery of the small molecule anionic drug, ascorbic acid from the chitosan‐conjugated PHEMA. Chitosan immobilization improves drug loading efficiency and induces sustained release of ascorbic acid. The chitosan modified hydrogel also reduces the biofouling of tear fluid components. Our results showed that surface modification by chitosan inhibits protein and bacterial deposition on the contact lens. Protein absorption analysis revealed that neat PHEMA adsorbed tear proteins at a density of 28.4 ± 4.4 μg/cm 2, whereas the chitosan‐conjugated hydrogel adsorbed tear proteins at a density of 18.5 ± 1.8 μg/cm 2 . Moreover, the neat PHEMA bacterial adhesion had a mean CFU value of 273 ± 27. However, a significant decrease in the number of bacterial colonies was observed in the chitosan group with a CFU value of 9 ± 6.